(untitled) (Revista LIDER, 2020)
The Orinoco Delta has changed little in its natural and human geography; however, during the last century, it has undergone some transformations. In this paper, we describe the original groups of marine collectors and horticulturalists, who settled in the periphery of the Orinoco delta. We then analyze some of the changes that have affected the way of life since the introduction of Chinese taro or ure (Colocasia esculenta) and the construction of a dam in the Southwestern Delta.